2008
DOI: 10.7863/jum.2008.27.8.1157
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Ultrasound-Guided Versus Fluoroscopically Guided Contrast-Controlled Piriformis Injections

Abstract: In this cadaveric model, ultrasound-guided piriformis injections were significantly more accurate than fluoroscopically guided contrast-controlled injections. Despite the use of bony landmarks and contrast, most of the fluoroscopically attempted piriformis injections were placed superficially within the gluteus maximus. Clinicians performing piriformis injections should be aware of the potential pitfalls of fluoroscopically guided contrast-controlled piriformis injections and consider using ultrasound guidance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
74
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(77 citation statements)
references
References 12 publications
0
74
0
3
Order By: Relevance
“…A cadaver study showed that the accuracy of this method was only 30%, with most of the needle tip being positioned in the gluteus maximus muscle. 98 This is not surprising given the fact that the fluoroscopy technique does not allow direct visualization of the soft tissue. Ultrasound and computer tomography (CT) have the advantage of allowing direct visualization of the PM.…”
Section: Limitation Of the Current Techniquesmentioning
confidence: 99%
See 2 more Smart Citations
“…A cadaver study showed that the accuracy of this method was only 30%, with most of the needle tip being positioned in the gluteus maximus muscle. 98 This is not surprising given the fact that the fluoroscopy technique does not allow direct visualization of the soft tissue. Ultrasound and computer tomography (CT) have the advantage of allowing direct visualization of the PM.…”
Section: Limitation Of the Current Techniquesmentioning
confidence: 99%
“…98 There have been many reports of ultrasound-guided PM injection that describe similar techniques with minor variation. 36,80,[98][99][100] The technique described below is the author's preferred technique. 28 …”
Section: Ultrasound-guided Injectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Siyatik sinir ile piriformis kasının anatomik ilişkisi ile ilgili varyasyonlar nedeniyle körleme yerine guideline eşliğinde enjeksiyonlar tercih edilmeye başlanmıştır. Ultrasonografi, BT, MRG, floroskopi ve EMG eşliğinde yapılan enjeksiyonların başarılı olduğuna dair çeşitli yayınlar mevcuttur [16][17][18][19] . Huerto ve ark.…”
Section: Tedaviunclassified
“…Other uses of ultrasound within CNS rehabilitation include neurotoxin injections for cervical dystonia, primary dystonia, and piriformis syndrome, as well as being an effective means to assess shoulder pathology in wheelchair users with spinal cord injury and early arthritic changes in patients with hemiparesis following stroke [57][58][59].…”
Section: Central Nervous System Rehabilitationmentioning
confidence: 99%